Report of the rural agricultural sample survey in the Oyo State of Nigeria 1980 - Nigeria. Oyo State; Oyo State (Nigeria). (Ibadan, Nigeria : Ministry of Economic Planning, Statistics Division, 1980)
This report is the 5th series of the annual publication on rural agriculture sample survey in oyo state. The data relates to only rural farming and provides information on the basic farming activities in the rural areas.
nmn 05/04/19
Loans
Keywords: Agriculture; Agricultural surveys; Rural agriculture; Oyo State, Nigeria